Analysis of four silvopastoral systems in Peru: Physical and nutritional characterization of pastures, floristic composition, carbon and CO2 reserves - Vásquez, Héctor (2020)
Four silvopastoral systems (SPS) and a system without tress were identified to measure variables such as: fresh matter, dry matter and floristic composition (dry and rainy season); nutritional composition; biomass: arboreal, herbaceous, litter and organic soil carbon (two depths), to determine total carbon and CO2. The greatest growth was recorded by the SPS Aliso pastures in both seasons and obtained the highest dry matter yield (0.27 kg/m2). In the rainy season, the greatest amount of grasses was for the SPS with Cypress (49%) and in weeds the SPS Pona (49%) and in the dry season the greatest amount of grasses was for the SPS Pino (52%) and in weeds SPS Pona (53%); predominantly Dactylis glomerata, Lolium multiflorum and Trifolium repens in both periods. In nutritional composition and digestibility, the SPS Aliso (crude protein (16.06%), neutral detergent fiber (48.23%) and digestibility (66.14%)) stood out. The highest carbon and CO2 retention was recorded in the SPS with Pona (179.49 t/ha and 658 t/ha) and the lowest was Alder (108.15 t/ha and 396.46 t/ha); As for the SWT, it obtained an amount of C of 131.33 t/ha and 481.44 t/ha of CO2. The SPS accumulated more carbon in the tree part and soil.